Search for CP violation using T^-odd correlations in B0→p[bar]pK+π− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2023)
A search for CP and P violation in charmless four-body B0→p¯pK+π− decays is performed using triple-product asymmetry observables. It is based on proton-proton collision data collected by the LHCb experiment at center-of-mass energies of 7, 8 and 13 TeV, corresponding to a total integrated luminosity of 8.4 fb−1. The CP- and P-violating asymmetries are measured both in the integrated phase space and in specific regions. No evidence is seen for CP violation. P-parity violation is observed at a significance of 5.8 standard deviations.